Prototipo de estimulador electrónico para ser utilizado en colostomía - Sagahón Martínez., M.; Villalobos Rojas., C.; Award., R. A. (Revista Mexicana de Ingenieria Biomedica, 2009)
The need to rehabilitate the muscles of a colostomy through electrical stimulation, using a portable instrument, to regaining contingency is of great necessity for colostomized patients. In 1994, Awad and Luna developed a straight-anal simulator that shows the power and pressure variations in the rectum and the internal anal sphincter. In 2000, Riedy et al1. used a battery-powered stimulator to stimulate the sphincter muscle, with a stream of 0-100 mA and 35 Hz. In 2005, Awad et al. They developed a virtual simulator of colon mechanics with computer programs. In 2006, Awad and Sagahón2 developed a device to stimulate the visceral smooth muscle in a colostomy for to regaining voluntary continent. The purpose was to design and build a portable 3 variables electronic stimulator (pressure, voltage and current). We design a prototype portable stimulator of 3 variables controlled by a pressure sensor. The current and voltage of the equipment were calibrated using a digital multimeter, and frequency using a digital oscilloscope. The design, development and assembly of the electronic stimulator will be used in the experimental animal colostomy model, evaluating and controlling pressure, voltage and frequency variables